Atomistic consideration of earth-abundant chalcogenide materials for photovoltaics: Kesterite and beyond. Issue 23 (12th October 2018) - Kim, Jekyung; Larina, Liudmila; Chung, Sung-Yoon; Shin, Donghyeop; Shin, Byungha
Abstract: Abstract : Despite the potential as a promising alternative to CdTe and Cu(In, Ga)Se2, the kesterite compound Cu2 ZnSn(S, Se)4 (CZTSSe) presents a critical challenge mainly from its high open-circuit voltage ( V oc ) deficit. Indeed, the V oc of the record CZTSSe solar cell to date has accounted for only 61% of that calculated by the Shockley–Queisser limit, whose origin can be ascribed to nonradiative recombination from a high density of defects and secondary phases. Therefore, an atomistic understanding and characterization of CZTSSe is highly essential to overcoming the current shortcomings in kesterite. This review discusses the advanced characterization techniques for studying the intrinsic properties of kesterite at a nanometer scale. Moreover, a cation substitution with an ionic mismatch around constituents is recognized as an effective route to address the fundamental limit (i.e., the cationic disorder) in CZTSSe. Here, we review recent studies on a novel chalcogenide Cu2 BaSn(S, Se)4 that substitutes Zn with Ba and results in less cationic disordering.